1998
DOI: 10.1002/(sici)1521-379x(199812)50:11/12<478::aid-star478>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Ageing of Starch Based Systems as Observed with FT-IR and Solid State NMR Spectroscopy

Abstract: The retrogradation and physical ageing of model starch systems with respect to their glass transition temperatures Tg have been investigated by Fourier transform infrared Spectroscopy and solid state NMR spectroscopy. Diffuse reflectance Fourier transform infrared (DRIFT) spectra demonstrate the commencing retrogradation of starch materials stored above their Tg by changes in peak lineshapes and intensities in the characteristic area between 995 cm−1 and 1020 cm−1. Solid state NMR proton relaxation times in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
10

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(71 citation statements)
references
References 0 publications
4
57
0
10
Order By: Relevance
“…FTIR Spectroscopy X-ray diffraction is a long-range technique and this information should be complemented with other methodologies such as FTIR spectroscopy, where the conformational changes at starch molecular level may be analyzed. In this technique, the bands at 1047 and 1022 cm −1 are characteristic of the crystalline and amorphous zones of the starch, respectively [22]. The band at 1040 cm −1 is related to the development of double helices that are formed in the early hours of storage of starchy products, while the band at 1053 cm −1 increases with longer storage times and is due to aggregation and crystallization of starch chains [23].…”
Section: X-ray Diffraction Studymentioning
confidence: 99%
“…FTIR Spectroscopy X-ray diffraction is a long-range technique and this information should be complemented with other methodologies such as FTIR spectroscopy, where the conformational changes at starch molecular level may be analyzed. In this technique, the bands at 1047 and 1022 cm −1 are characteristic of the crystalline and amorphous zones of the starch, respectively [22]. The band at 1040 cm −1 is related to the development of double helices that are formed in the early hours of storage of starchy products, while the band at 1053 cm −1 increases with longer storage times and is due to aggregation and crystallization of starch chains [23].…”
Section: X-ray Diffraction Studymentioning
confidence: 99%
“…X-ray diffraction studies clearly showed that the development of crystallinity occurred in an aging starch gel . Nevertheless, the sensitivity of this method was too low to detect the minor extent of recrystallization during a rapid storage (Smits, Ruhnau, Vliegenthart, & van Soest, 1998). Differential scanning calorimetry (DSC) was apparently used for measuring retrogradation of starch and proved to be a valuable tool to quantify the crystallinity of amylopectin rather than amylose recrystallite since this recrystallite was transformed at much higher temperature (120-160°C), at which the pans would be leaked before the transition occurred (Eerlingen, Jacobs, & Delcour, 1994;Russell, 1987).…”
Section: Introductionmentioning
confidence: 77%
“…These findings also suggest that the band can be considered as characteristic for the type of Metal-Ligand links. The band at about 1042 and 1019 cm -1 found for polysaccharide in the spectra of RLMP and the complex were shown to relate to the crystalline and amorphous phases, respectively (Smits et al, 1998). The changes in intensity of these bands are strongly associated with the alterations in the macromolecular order.…”
Section: Resultsmentioning
confidence: 99%